Awareness and efficacy of police-community affairs and development program in bula, camarines sur - Ama, Manny G. (San Miguel, Iriga City: University of Saint Anthony, 2024)
Awareness and efficacy of police-community affairs and development program in bula, camarines sur.
Includes bibliographical references.
English
Keywords: Police-community.